Minimization of Threshold-Current Dependence of Quantum Dot Laser Using InN - M. A. Humayun; M. A. Rashid; M. Abdul Malek (IAES Indonesian Section, 2019)
This paper focuses on the effect of threshold current density on different characteristics of quantum dot based laser. To investigate the effect, different characteristics have been analyzed using quantum dot as the active layer material of the laser structure. Performance improvement of quantum dot laser using InN has been achieved in terms of minimization of the threshold current dependence such as mirror loss, modal gain, turn-on delay and so forth. Numerical results have been analyzed considering the values of threshold current densities of GaN, AlN and InN based quantum dot lasers. Analytical results show that internal loss increases linearly with the increase of the threshold current density. However, other characteristics like mirror loss, modal gain, turn-on delay have nonlinear dependence on the threshold current density for any material used in the active layer. The threshold current density of InN quantum dot based laser is lower than that of other existing quantum dot based lasers. Analytical results ascertained that mirror loss has been increased a little bit. Conversely, internal loss and modal gain have been minimized considerably using InN based quantum dot in the active layer of the laser structure. In addition, turn-on delay time has been also minimized significantly.